Iatrogenic Genitourinary Fistula: Changing Trends - Pradhan, T; Agrawal, A; Regmi, MC (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To study the frequency of iatrogenic cause amongst the surgery done for genitourinary fistula and to study the type and cause of iatrogenic genitourinary fistula. Methods: This is a 5 year retrospective study analyses 73 iatrogenic fistulas from 217 women undergoing surgery for genitourinary fistula repair from year 2013 to 2018 on going. The analysis considers frequency and characteristics of type of fistula. Results: Out of 217 genitourinary fistula 73(33.6%) were iatrogenic. Vaginal vault fistulas were 54.7% followed by ureteric fistula 32.8%, vesicovaginal fistula 10.9% and there were 2 iatrogenic RVF. The frequency of surgeries for iatrogenic fistula were found to be in increasing trend towards current years and 83.5% of the iatrogenic fistula were found with history of hysterectomy followed by emergency caesarean section 16.4%. Conclusions: Women undergoing hysterectomy were under risk for iatrogenic fistula. Optimum work environment is important to reduce surgical error during procedures. Operating training should be emphasized on optimal surgical skills, decision making.